Tourism Destination Experience and Local Wisdom as Drivers of Electronic Word of Mouth: The Mediating Role of Tourist Satisfaction in Kabupaten Sikka. - Yoseph Darius Purnama Rangga; Yosef Tonce; Nunsio Handrian Meylano; Laura Maria Jeanne Odang; Antonius Philipus Kurniawan Gheta; Yohanes Mbani (Penerbit Goodwood, 2026)
Purpose: This study examines the influence of tourism destination experience and local wisdom on tourists’ Electronic Word-of-Mouth (E-WOM), with tourist satisfaction as a mediating variable. Methodology: Grounded in Expectancy Disconfirmation Theory, this study employed a quantitative approach using a survey of 210 repeat visitors to tourist destinations in Sikka District, Nusa Tenggara Timur, Indonesia. Data were collected using structured questionnaires and analyzed to test the relationships among the variables. Results: The findings indicate that tourism destination experience and local wisdom do not significantly directly affect E-WOM. However, tourist satisfaction has a significantly positive effect on E-WOM. Additionally, both tourism destination experiences and local wisdom significantly influence tourist satisfaction. Mediation analysis showed that tourist satisfaction fully mediated the relationship between tourism destination experience and E-WOM, as well as between local wisdom and E-WOM. Conclusions: Tourist satisfaction plays a crucial role as a mediating mechanism linking tourism experiences and local cultural values to tourists’ willingness to share their experiences online. Limitations: This study is limited by a sample dominated by young domestic tourists and the use of a cross-sectional research design. Contributions: This study contributes to the tourism marketing literature by highlighting the mediating role of satisfaction and providing practical insights for enhancing digital promotion strategies through E-WOM.